2008
DOI: 10.1007/s00198-008-0657-4
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of radiographic vertebral fractures in Latin American countries: the Latin American Vertebral Osteoporosis Study (LAVOS)

Abstract: We conclude that radiographically ascertained vertebral fractures are common in Latin America. Health authorities in the region should be aware and consider implementing measures to prevent vertebral fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
3
36

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 14 publications
9
75
3
36
Order By: Relevance
“…The major finding of this study was that approximately one in four postmenopausal women in apparently good health, but with reduced SI, had sustained at least one vertebral fracture. In accordance with previous surveys, we found that the prevalence and the severity of vertebral fractures in such women increase steadily with age [4,7,10,13,24,27,31,35]. In addition, we found the presence of an undiagnosed osteoporotic vertebral fracture was an independent risk factor for inferior quality-of-life scores using the QUAL-EFFO tool.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The major finding of this study was that approximately one in four postmenopausal women in apparently good health, but with reduced SI, had sustained at least one vertebral fracture. In accordance with previous surveys, we found that the prevalence and the severity of vertebral fractures in such women increase steadily with age [4,7,10,13,24,27,31,35]. In addition, we found the presence of an undiagnosed osteoporotic vertebral fracture was an independent risk factor for inferior quality-of-life scores using the QUAL-EFFO tool.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, in the European Vertebral Osteoporosis Study (EVOS), the prevalence of fractures in postmenopausal women aged 50 to 79 years, randomly recruited from the general population, varied from 12.0% to 20.2% according to the McCloskey and Eastell method, respectively, and from 11.1% to 20% according to geographic differences [27]. Also, Clark et al [4] in an agestratified random sample of women aged 50 years or older from South America found a prevalence increasing from 6.9% in women aged 50 to 59 years to 27.8% in those aged 80 years or older. This difference may be the result of the fact that the age of our study population was a minimum of 60 years and that the morphometric evaluation was carried out only on those women with a quantitative ultrasound t-score B À2.0 and therefore with a mild increase in fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that in Brazil 2/3 of this population has low bone mass or osteoporosis (17) and based on our data, a reasonable estimate projects an increase in the number of new vertebral fractures from 60,000 in 2013 to more than 188,000 in 2060.…”
Section: Discussionmentioning
confidence: 70%
“…The Latin American Vertebral Osteoporosis Study (LAVOS) evaluated a randomized sample of 1,922 women aged 50 years and older from Argentina, Brazil, Colombia, Mexico, and Puerto Rico (22). The preva lence of vertebral fractures as assessed by lateral Xrays of the lumbar and thoracic spine was 11.18%, and was similar in the five countries.…”
Section: Prevalence Of Osteoporosis In Brazilmentioning
confidence: 99%